Anatomy of spinal nerves in the first Turkish illustrated anatomy handwritten textbook - Çetkin, Murat; Orhan, Mustafa; Bahşi, İlhan; Turhan, Begümhan (Springer Verlag, 2016)
“Teşrih-ül Ebdan ve Tercümânı Kıbale-i Feylesûfan” is the first handwritten anatomy textbook with illustrations written in Turkish in 17th century by Şemseddîn-i İtâḳî. “Teşrih” has different meanings such as anatomy, skeleton, and cutting a corpse into pieces [1]. “Teşrih-ül Ebdan ve Tercümânı Kıbale-i Feylesûfan ” means dissection of the body and scholars’ birth knowledge [2]. Since this is the first handwritten textbook in Turkish, it has great importance in the development of medicine in Ottoman Empire. This book was written while Grand Vizier Recep Pasha was in power, and it was dedicated to the Sultan of that period, Murat the IVth [3, 4]. It is thought that the book was written in 1632
Keywords: Anatomy of spinal; illustrated anatomy; textbook